2010
DOI: 10.1177/0275074010377654
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of E-Communication Applications in U.S. Municipalities: The Role of Political Environment, Bureaucratic Structure, and the Nature of Applications

Abstract: E-government has been touted by many as a technological answer to improve citizen participation, government accountability, and transparency by facilitating a greater level of communication and flow of public information between citizens and the government. This article examines how political environment, government structure, and the nature of individual e-government applications influence the likelihood of adoption. Using data obtained from multiple sources, logistic regressions are conducted on a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 21 publications
3
66
2
3
Order By: Relevance
“…ICTs in general and government websites in particular have the potential to create new forms of dialogue and informal interaction that enable greater involvement and participation of citizens in matters that affect them directly (Kaye and Johnson 2002;Pina et al 2010;Ahn 2011). Information available on government websites revitalizes the democratic process to create an electronic public square that allows citizens to contact with each other and with their rulers directly, increasing public access to information and contributing to create a more informed citizenry (Kaye and Johnson 2002).…”
Section: A Literature Background On Transparency and Its Implicationsmentioning
confidence: 99%
“…ICTs in general and government websites in particular have the potential to create new forms of dialogue and informal interaction that enable greater involvement and participation of citizens in matters that affect them directly (Kaye and Johnson 2002;Pina et al 2010;Ahn 2011). Information available on government websites revitalizes the democratic process to create an electronic public square that allows citizens to contact with each other and with their rulers directly, increasing public access to information and contributing to create a more informed citizenry (Kaye and Johnson 2002).…”
Section: A Literature Background On Transparency and Its Implicationsmentioning
confidence: 99%
“…The first municipal resource is organisational size (Walker, 1969;Weare et al, 1999;Ahn, 2011). Larger organisations are generally more inclined to adopt innovations than smaller organisations, because they have greater financial resources and more human resources.…”
Section: Resourcesmentioning
confidence: 99%
“…So far diffusion research at the local level has mainly concentrated on voluntary adoption of innovations (for example, Sugiyama, 2008;Hansen, 2011;Krause, 2011;Walker et al, 2011). A considerable amount of research focusing on e-government (related) innovations has also been carried out at the local level (for example, Weare et al, 1999;Moon, 2002;Norris and Moon, 2005;Ahn, 2011;Homburg et al, 2013). In this article we aim to contribute to a better understanding of innovation in local government in a decentralised system by examining patterns of adoption of a mandated e-government innovation in Dutch municipalities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that organizational factors such as centralization, work routineness, formalization, and complexity are related to innovation adoption (Ahn, 2011;Tornatzky & Fleischer, 1990). In the case of e-government, for example, Li and Feeney (2012) find that both routineness and organization centralization are negatively related to the adoption of e-services.…”
Section: Organizational Culturementioning
confidence: 99%